FILLER ENGINEERING IN WOOD–PLASTIC COMPOSITES: A REVIEW OF MECHANICAL PERFORMANCE, INTERFACIAL BEHAVIOR, AND FAILURE MECHANISMS - Cahyo Budiyantoro; Johanes Wawan Joharwan (RADJA PUBLIKA, 2026)
Wood–plastic composites (WPCs) have gained increasing attention as lightweight, cost-effective, and sustainable materials for applications such as construction, furniture, automotive components, and consumer products. Among the variables affecting WPC performance, filler characteristics play a central role by controlling stress transfer, interfacial adhesion, stiffness, strength, and fracture behaviour. This literature review examines the influence of filler characteristics on the mechanical performance of WPCs. The discussion includes filler type and source, particle size, particle shape, aspect ratio, filler loading, raw material composition, and chemical pretreatment, together with their interactions with coupling agents and polymer matrices. The reviewed studies show that these factors strongly influence tensile strength, flexural strength, modulus, impact resistance, and failure mechanisms. Differences in wood species, recycled lignocellulosic materials, and agricultural residues also contribute to variations in composite behaviour, driven by their distinct chemical composition, density, morphology, and thermal stability. In addition, surface modification and compatibilisation, especially using maleic anhydride-grafted polyolefins, are widely reported to improve filler–matrix adhesion and mechanical properties. Overall, WPC optimisation requires integrated control of filler morphology, composition, content, and interface quality.